Sector-Based Action Against Corruption - Pyman, Mark. author. aut Link
XXI, 182 p. 31 illus.
Keywords: This open access book provides an accessible insight into how to tackle corruption in organisations and institutions. It explains how to recognise and analyse corruption issues, together with knowledge and advice on how they can be avoided, prevented, or minimised. It also provides a framework through which readers can examine what strategies are available to tackle corruption issues, a rationale for how to prioritise strategies depending on circumstances and context, and guidance on how to critique various options. The book will appeal to professionals and practitioners, as well as academics interested in governance and corruption. Mark Pyman is co-founder of the online network CurbingCorruption.com, having previously created and led Transparency International’s global programme tackling defence and security corruption. He served as a Commissioner in Afghanistan’s Anti-Corruption Committee (MEC). Paul M. Heywood holds the Sir Francis Hill Chair of European Politics at the University of Nottingham, UK. His research focuses on political corruption, institutional design, and state capacity. With Mark, he is also co-founder of the online network CurbingCorruption.com.